Exploration of changes in disability after menopause in a longitudinal multiple sclerosis cohort - Bove, Riley; Healy, Brian C; Musallam, Alexander; Glanz, Bonnie I; De Jager, Philip L; Chitnis, Tanuja (Multiple sclerosis, 2016)
Onset of multiple sclerosis (MS) is typically in early adulthood. The impact, if any, of menopause on the MS course is unknown. Our objective was to determine whether menopause is associated with changes in MS severity in a longitudinal clinical cohort. Responses from an ongoing reproductive questionnaire deployed in all active female CLIMB observational study participants with a diagnosis of clinically isolated syndrome (CIS) or MS were analyzed when the response rate was 60%. Reproductive data were linked with clinical severity measures that were prospectively collected every six months, including our primary measure, the Expanded Disability Status Scale (EDSS). Over one-half of the respondents (368 of 724 women) were postmenopausal. Median age at natural menopause was 51.5 years. In our primary analysis of 124 women who were followed longitudinally (mean duration 10.4 years) through their menopausal transition (natural or surgical), menopause represented an inflection point in their EDSS changes (difference of 0.076 units; 95% CI 0.010-0.14; p = 0.024). These findings were not explained by vitamin D levels, nor changes in treatment or smoking status over this period. There was no effect of hormone replacement therapy (HRT) exposure, but HRT use was low. We observed a possible worsening of MS disability after menopause. Larger cohorts are required to assess any HRT effects.